The effects of Wal-Mart on local labor markets - David Neumark; Junfu Zhang; Stephen Ciccarella (Institute for the Study of Labor (IZA), 2007)
We estimate the effects of Wal-Mart stores on county-level retail employment and earnings, accounting for endogeneity of the location and timing of Wal-Mart openings that most likely biases the evidence against finding adverse effects of Wal-Mart stores. We address the endogeneity problem using a natural instrumental variables approach that arises from the geographic and time pattern of the opening of Wal-Mart stores, which slowly spread out from the first stores in Arkansas. The employment results indicate that a Wal-Mart store opening reduces county-level retail employment by about 150 workers, implying that each Wal-Mart worker replaces approximately 1.4 retail workers. This represents a 2.7 percent reduction in average retail employment. The payroll results indicate that Wal-Mart store openings lead to declines in county-level retail earnings of about 1.2 million, or 1.3 percent. Of course, these effects occurred against a backdrop of rising retail employment, and only imply lower retail employment growth than would have occurred absent the effects of Wal-Mart.
urn:nbn:de:101:1-20080425510
Keywords: 330; Einzelhandel; Beschäftigung; Regionaler Arbeitsmarkt; Filiale; USA